Spectrum of Congenital Heart Disease in Neonates Admitted in an Intermediate Care Unit of a Tertiary Level Hospital - Chapagain, Ram Hari; Shrestha, Needa; Kayastha, Madhusudhan; Shakya, Sheelendra; Adhikari, Kimat; Shrestha, Sushan Man (Journal of Nepal Paediatric Society, 2018)
Introduction: Congenital Heart Disease is the most common cause of major congenital anomalies accounting 28.0%, representing a major global health problem. Prevalence of Congenital Heart Disease is 1.3 per 1000 in school children of Nepal. Material and Methods: A cross sectional prospective study was carried out in the neonatal intermediate care unit of Kanti Children’s Hospital, Nepal from Jan 2016 until Dec 2016 to see the spectrum of CHD. Results: Out of admitted 831 neonates, 85 were found to have CHD with prevalence of 102.28 per 1000 admitted neonate. Respiratory distress was the commonest symptom (51.8%) followed by cyanosis (11.8%) and reluctant to feed (10.6%) at presentation. ASD was the commonest (87.1%) cases followed by PFO 23.5%, PDA 21.2%, Complex congenital heart disease 11.8% and TOF 1.2%. Cleft lip and Cleft Palate was found in 5.9%, Down’s syndrome 3.5% of cases, polydactyly and syndactyly was detected in 2.4% newborn with CHD. The mode of delivery was spontaneous in 71.8% followed by Elective LSCS were 14.1% and Emergency LSCS were 9.4%. Conclusions: Prevalence of CHD was the 102.28 per 1000 neonates admitted in NIMCU. Atrial Septal Defect was the commonest congenital heart diseases. Cleft lip and Down’s syndrome were the most extra cardiac anomaly associated with CHD. Respiratory distress was the commonest presentation of CHD for hospital admission.